Strategi Penerapan Pendekatan Contextual Teaching And Learning dalam Pembelajaran Fiqih di MI As Sidqiyah Siak: Strategies for Implementing Contextual Teaching and Learning Approach in Learning Fiqh at MI As Sidqiyah Siak - Maryani, Maryani (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to determine the application of Contextual Teaching and Learning (CTL) learning strategies in Fiqh subjects at MI As Sidiqiyah Siak, as well as supporting and inhibiting factors in its implementation. This research uses a qualitative approach with descriptive methods. The research data sources consisted of Fiqh teachers, madrasah heads, and students. Data collection techniques were carried out through observation, interviews, and documentation, and used triangulation of techniques and sources for data validity. The results showed that the application of CTL strategies in MI As Sidiqiyah Siak can facilitate teachers in linking learning materials with students' real lives, motivating students to be more active and critical, and helping students develop knowledge learned in the context of everyday life. In addition, Fiqh learning implemented through CTL strategies can improve the attitude of cooperation between students and teachers, as well as between students with each other. The main supporting factors in the application of CTL are the support of teachers, parents, and adequate educational resources, while the inhibiting factors include the lack of student discipline and the lack of parental guidance. Overall, the CTL strategy proved to be effective in improving students' understanding of Fiqh material and forming positive attitudes in their daily lives.